ChemInform Abstract: Conversion of Ester Moieties to 4‐Bromophenyl Groups via Electrocyclic Reaction of Dibromocyclopropanes. Issue 46 (November 2015) - Ueda, Kyosuke; Umihara, Hirotatsu; Yokoshima, Satoshi; Fukuyama, Tohru
Abstract The utility of this method is demonstrated in the conversion of lactone (VIII) to compound (IX).